Ventricular fibrillation amplitude analysis and comparison for transvenous ICD and extravascular ICD systems. (14th October 2021) - Liu, Y; Majumder, S; Zhang, X.S; Degroot, P; Liang, S
Abstract: Background: Transvenous (TV) implantable cardioverter-defibrillator (ICD) and extravascular (EV) ICD have very different electrode configurations (Figure 1). TV ICD has direct contact with the heart via endocardial lead placement with a nominal Tip-Ring sensing vector, whereas EV ICD utilizes a lead placed substernally outside the heart, with S1-S2 sensing vector as the nominal. Different lead and electrode locations result in different electrogram (EGM) signal amplitude and variability. Small ventricular fibrillation (VF) amplitude may lead to undersensed VF. Purpose: The purpose is to characterize the VF amplitude from nominal sensing vector for TV ICD and EV ICD. Methods: For TV ICD, 435 VF segments from Tip-Ring vector in 80 patients were analyzed. For EV ICD, 72 VF segments from S1-S2 vector in 32 patients were analyzed. For each VF segment, 1-second moving window with 50% overlapping was used to calculate maximum rectified (MR) VF amplitude. We calculated the maximum, minimum, mean, and standard deviation of averaged MR amplitude for all the episodes for each vector. The percentage of episodes with averaged MR amplitude smaller than different amplitude thresholds was also computed for each of the two vectors. Results: VF signals from EV ICD had smaller averaged MR amplitude than TV ICD: S1-S2 = 3.05±1.62 mV versus Tip-Ring = 6.98±2.10 mV. EV ICD had 65% of episodes above 2.00 mV vs. 96% for TV ICD. The VF amplitude for EV ICD also had a smaller range than TV ICD: 0.47–8.43 mV versus 0.88–16.00mV. Despite having smaller amplitude, recordings of all VF episodes for both systems met detection criteria with no clinically significant delay. Conclusions: Without direct myocardial contact, mean VF EGM amplitude from EV ICD system is approximately 44% of that for the TV ICD system. But with less variability across patients, it is more likely that a single (nominal) sensitivity setting will be effective among the population with EV ICD. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic